PERAN SATUAN BINMAS DALAM SISTEM BINA KUSUMA GUNA MENEKAN ANGKA PREMANISME DI WILAYAH HUKUM POLRES CIMAHI - Rio Arya Mulyawarman (Advances in Police Science Research Journal, 2020)
In life and community life, everyone will experience social change. Various social changes that occur are a general phenomenon that will inevitably occur wherever humans will settle. Social dynamics that occur in society have an impact on the development of society to enter deeper into the more modern phases of human life which will not only bring good effects to human life itself but also indirectly will bring negative impacts as well, such as developing and increasing various types and forms of crime that did not exist before. One of the phenomena of social problems that occur in society is acts of gangsterism which often unsettles and gives fear to the community. The Binmas Unit has the role to conduct prevention through Operation Bina Kusuma where the target is perpetrators of thuggery. However, in the last three years there has been an increase in thuggery in the jurisdiction of the Cimahi Police Station. From the description above, the author is interested in examining the role of the Binmas Unit in Bina Kusuma Operations from a number of problem formulations, namely the role of the Binmas Unit in reducing thuggery by using the Bina Kusuma Operation system, and internal and external factors that affect the Bina Kusuma Operation system by the Binmas Unit . Conceptual literature contains two research results that are relevant to this study. The theory that the writer uses in this research is based on communication theory, role theory, SWOT theory, needs hierarchy theory, counseling guidance concept, Binmas Unit concept, and Operation Bina Kusuma concept. The approach used by the authors in this study is a qualitative approach and the type of research is field study. The focus of the study was on the role of the guidance counseling of the Community Service Unit at Cimahi Regional Police Station. The sources used are primary and secondary sources. Data collection techniques used in this study were interviews, observation and document study. The author uses triangulation techniques in determining the validity of the data. Data analysis techniques used are data reduction, data presentation, and conclusions. The factors that influence Operation Bina Kusuma are internal factors such as lack of members, lack of coordination with other functional units and external factors such as lack of coordination with relevant outside agencies. The findings obtained by the authors during the study were that the Binmas Unit personnel had not yet followed the Dikjur, the budget to carry out the tasks in accordance with the Bina Kusuma Operation, the role of the Binmas Unit was not maximal in the implementation of its duties due to the number of members, lack of coordination with other functional units, so conducting Bina Kusuma Operations tends to have no impact on perpetrators of thuggery and there is no clear cooperation with other agencies. The author's suggestion is to foster members through education and education, recruitment of young non-commissioned officers and support staff to make new breakthroughs in carrying out Operational Bina Kusuma tasks based on priority scale, as well as making written cooperation, so as to create a conducive Harkamtibmas situation at the Cimahi Regional Police Station.